2018
DOI: 10.4049/jimmunol.1800683
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Humoral Alloimmunity from Differences in Donor and Recipient HLA Surface Electrostatic Potential

Abstract: In transplantation, development of humoral alloimmunity against donor HLA is a major cause of organ transplant failure, but our ability to assess the immunological risk associated with a potential donor–recipient HLA combination is limited. We hypothesized that the capacity of donor HLA to induce a specific alloantibody response depends on their structural and physicochemical dissimilarity compared with recipient HLA. To test this hypothesis, we first developed a novel computational scoring system that enables… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 92 publications
(110 reference statements)
1
26
0
Order By: Relevance
“…For other important antigens with known structures in the PDB, such features can be derived from an annotated database connecting pMHC-I/TCR co-crystal structures with biophysical binding data (41), and were recently employed in an artificial neural network approach to predict the immunogenicity of different HLA-A*02:01 bound peptides in the context of tumor neoantigen display (42). A separate study has shown that the electrostatic compatibility between self vs foreign HLA surfaces can be used to determine antibody alloimmune responses (43). Given that antibodies and TCRs use a common fold and similar principles to engage pMHC-I molecules (40), it is likely that surface electrostatic features play an important role in recognition of peptide/HLA surfaces by their cognate TCRs in the context of SARS-CoV-2 infection.…”
Section: Resultsmentioning
confidence: 99%
“…For other important antigens with known structures in the PDB, such features can be derived from an annotated database connecting pMHC-I/TCR co-crystal structures with biophysical binding data (41), and were recently employed in an artificial neural network approach to predict the immunogenicity of different HLA-A*02:01 bound peptides in the context of tumor neoantigen display (42). A separate study has shown that the electrostatic compatibility between self vs foreign HLA surfaces can be used to determine antibody alloimmune responses (43). Given that antibodies and TCRs use a common fold and similar principles to engage pMHC-I molecules (40), it is likely that surface electrostatic features play an important role in recognition of peptide/HLA surfaces by their cognate TCRs in the context of SARS-CoV-2 infection.…”
Section: Resultsmentioning
confidence: 99%
“…As we work to disentangle and acquire a more nuanced understanding of additional and specific risk factors that may influence the development of dn DSAs or GVHD, the ultimate goal would be to integrate all relevant factors into a comprehensive risk analysis scheme. Specifically, this integrative approach would likely include both quantitative and qualitative components, reflecting numbers of epitope mismatches as well as immunogenicity of each specific epitope (whether based on physicochemical 11,20,5053 or other characteristics and/or capacity of epitopes to be presented by the responder’s HLA molecules 54,55 ), levels of expression of these epitope-containing HLAs, as well as aspects of their regulation in various contexts. It is possible that additional metrics may be included in the future.…”
Section: Discussionmentioning
confidence: 99%
“…epitope load) (Mallon et al, 2015). While epitope load can be predicted by sequence-based epitope analysis, Mallon et al (2014), Mallon et al (2018) suggest that surface electrostatic properties are a better predictor of immunogenic potential. The electrostatic interactions between molecules can mediate high-affinity antibody-antigen binding and have a putative role in antibody affinity maturation (Mallon et al, 2014).…”
Section: Surface Electrostatic Potentialmentioning
confidence: 99%